2014
DOI: 10.1016/s0140-6736(13)61905-4
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical and cost-effectiveness of cognitive behaviour therapy for health anxiety in medical patients: a multicentre randomised controlled trial

Abstract: National Institute for Health Research Health Technology Assessment Programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
127
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(149 citation statements)
references
References 26 publications
2
127
1
1
Order By: Relevance
“…Pharmacological treatment is not normally acceptable to patients, as those with marked health anxiety are typically very sensitive to adverse effects of medication: but fluoxetine showed some benefit over placebo, though this was not pronounced and occurred late in treatment (8-12 weeks [I (PCT)] (Fallon et al, 2008). Psychological treatments have been found beneficial [I (M)] ( Thomson and Page, 2007), and include behavioural stress management (Clark et al, 1998) ([II]), cognitive behaviour therapy, in both face-to-face and internet format (Hedman et al, 2011b;Seivewright et al, 2008;Sørensen et al, 2011) (Tyrer et al, 2014).…”
Section: Marked Health Anxiety ('Illness Anxiety Disorder')mentioning
confidence: 99%
“…Pharmacological treatment is not normally acceptable to patients, as those with marked health anxiety are typically very sensitive to adverse effects of medication: but fluoxetine showed some benefit over placebo, though this was not pronounced and occurred late in treatment (8-12 weeks [I (PCT)] (Fallon et al, 2008). Psychological treatments have been found beneficial [I (M)] ( Thomson and Page, 2007), and include behavioural stress management (Clark et al, 1998) ([II]), cognitive behaviour therapy, in both face-to-face and internet format (Hedman et al, 2011b;Seivewright et al, 2008;Sørensen et al, 2011) (Tyrer et al, 2014).…”
Section: Marked Health Anxiety ('Illness Anxiety Disorder')mentioning
confidence: 99%
“…Tests and confidence intervals for treatment effects would be based on the normal distribution -an assumption justified by the central limit theorem. Estimates for the standard deviation (SD) of HADS-A scores are available from Tyrer et al 50 In this study, SDs between 4 and 5 were found for the change of score between baseline and 12 months for both randomised conditions. Therefore, we used an estimate of 5 for the SD of our outcome measure, overlaid with an additional component of variance (essentially attributable to the therapist) sufficient to give an intracluster correlation coefficient of 0.02.…”
Section: Sample Size Calculationmentioning
confidence: 57%
“…Exploratory analyses would have been carried out to describe how patient preferences along with a limited number of other prespecified characteristics of participants may modify treatment effects. 50 Any subgroup analyses conducted would also have been regarded as exploratory.…”
Section: Primary Outcome Analysismentioning
confidence: 99%
“…71 CBT treatment for health anxiety was effective at 6 months, 1 and 2 years with no significant increase in costs for anxiety and depression, but was ineffective in increasing health-related QoL. 72 We are unsure what the difference is between the therapies that continue to be efficacious for affective symptoms and those that do not, but our intervention adds to the evidence that therapies can continue to be effective over years.…”
Section: Structured Psychological Treatment Of Depression In Other Grmentioning
confidence: 88%